Utilization of Acacia Leaves for Patients with Diabetes Mellitus, Cancer and Coronary Heart - Nurna Ningsih; Eprila; Ni Ketut Sujati; Lukman (Postgraduate, University of Mataram, 2023)
Free radicals can cause cell damage and also damage biomolecules, such as DNA, proteins, and lipoproteins in the body which can trigger degenerative diseases, such as diabetes mellitus, cancer, coronary heart disease. Acacia plant has been widely recognized as an antioxidant agent that removes free radicals which can prove a useful therapeutic tactic in controlling diabetes, cancer and coronary heart disease. This research method uses qualitative methods. This study aims to determine the use of Acacia Leaves for people with Diabetes Mellitus, Cancer and Coronary Heart. The results of this study found that acacia leaves contain lots of antioxidants which can treat diabetes mellitus, cancer and heart disease. Acacia leaves are very good for consumption by people with diabetes, cancer, and coronary heart because they contain saponins, flavonoids, polyphenols, and antimicrobials which are efficacious for reducing cholesterol and blood sugar levels